Immigrant small business and international economic linkage : A case of the korean wig business in Los Angeles, 1968-1977 - Chin, K. S.; Yoon, I. J.; Smith, D.
tbls., map.
pp. 485-510
Keywords: Estados Unidos de America; Coreanos; Inmigrantes; Asimilación; Hombres de Negocios; Mercado de Trabajo